2020
DOI: 10.1016/j.chom.2020.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Root-Secreted Coumarins and the Microbiota Interact to Improve Iron Nutrition in Arabidopsis

Abstract: Highlights d Coumarins alter the root microbiota and improve plant growth in iron-limiting soil d The microbiota improves plant iron nutrition via a coumarindependent mechanism d The iron-beneficial commensal trait is taxonomically widespread but strain specific d Coumarin-microbiota interaction resolves iron starvation and regulates immune response

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
177
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 254 publications
(199 citation statements)
references
References 64 publications
4
177
0
Order By: Relevance
“…Besides their function in the mobilization and uptake of iron from the soil environment, coumarins such as scopoletin, possess a selective antimicrobial activity (Stassen et al 2020;Stringlis et al 2019a). Using the mutant f6'h1, which is impaired in the coumarin biosynthesis gene FERULOYL-CoA 6'HYDROXYLASE1, it was shown that F6'H1-dependent coumarins have a significant effect on the composition of microbiota in the rhizosphere or in gnotobiotic conditions using microbial synthetic communities (Harbort et al 2020;Stringlis et al 2018b;Voges et al 2019). Interestingly, WCS417 was shown to be highly tolerant to the antimicrobial activity of the coumarin scopoletin, while the soil-borne fungal pathogens F. oxysporum and Verticillium dahliae were strongly inhibited in their growth when exposed to scopoletin in the growth medium (Stringlis et al 2018b).…”
Section: Among the Stars: Wcs417 In A Root Microbiome Contextmentioning
confidence: 99%
“…Besides their function in the mobilization and uptake of iron from the soil environment, coumarins such as scopoletin, possess a selective antimicrobial activity (Stassen et al 2020;Stringlis et al 2019a). Using the mutant f6'h1, which is impaired in the coumarin biosynthesis gene FERULOYL-CoA 6'HYDROXYLASE1, it was shown that F6'H1-dependent coumarins have a significant effect on the composition of microbiota in the rhizosphere or in gnotobiotic conditions using microbial synthetic communities (Harbort et al 2020;Stringlis et al 2018b;Voges et al 2019). Interestingly, WCS417 was shown to be highly tolerant to the antimicrobial activity of the coumarin scopoletin, while the soil-borne fungal pathogens F. oxysporum and Verticillium dahliae were strongly inhibited in their growth when exposed to scopoletin in the growth medium (Stringlis et al 2018b).…”
Section: Among the Stars: Wcs417 In A Root Microbiome Contextmentioning
confidence: 99%
“…In the “unavailable iron” condition, iron(III) (supplied as FeCl 3 ) is sparingly soluble and is unavailable to plants. This is critical for assessing nutritionally beneficial host-microbiota interactions, which are precluded in artificial systems where iron is removed altogether ( Harbort et al., 2020 ). As a control “available iron” medium with the same iron content and pH, the media is supplied with the same concentration of a chelated form of iron (FeEDTA, Ferric sodium ethylenediaminetetraacetate), which has increased solubility even in these alkaline conditions.…”
Section: Before You Beginmentioning
confidence: 99%
“…Example datasets and scripts for analysis from ( Harbort et al., 2020 ) have been deposited to Mendeley Data with the https://doi.org/10.17632/tkdn6zbw7k.1 .…”
Section: Resource Availabilitymentioning
confidence: 99%
See 2 more Smart Citations